(untitled) (Jurnal Manajemen Perhotelan, 2012)
Fire become such a serious risk for anyone staying in a high rise building. The risk tend to be double should either the developer and the users neglect on the issues. Fire which happened to a high rise building will be badly harmful compared to the other locations. The good awareness on the Fire danger of anyone occupying the building will be very useful for avoiding panic which some expert said as the main factor of either making people collapse or evacuation process goes very difficult to do. Good awareness will reflect to attitudes and later it will stimulate the behavior. High rise building occupant which has good awareness will behave theirselves at least being of not panic once the real fire happened, furthermore they will always find their way to protect and anticipate the fires.